DETERMINATION OF THE AMOUNT OF FLAVONOIDS IN PAULOWNIA AND ROSMARINUS PLANT LEAVES (Scientific journal of the Fergana State University, 2024)
In this study, the flavonoids contained in the leaves of Paulownia and Rosmarinus, which were introduced to our country and grow in the territory of Fergana region, were studied by the HLPC method. According to the analysis of the results of the studied plant samples, it was found that they contain 6 types of flavonoids.